Video Game Increases Depression in Students - Edith Humries; Budi Pratiti; Patricia Wulandari; Rachmat Hidayat (HM Publisher, 2020)
Introduction: The effects of exposure to violence in newspaper and electronic media to children and adolescents were being an awareness various parties, namely, researchers, health practitioners and policy makers. Depression is a mental problem that is always found due to exposure to video games. Methods: This study was an observational study with a cross-sectional research design. The subjects of the study were teenagers aged 15-18 years, students of Vocational School Yogyakarta, Indonesia. Data analysis was performed with IBM SPSS 16. Data analysis to assess the relationship between length and video game content with depression levels (Children’s Depression Inventory -2) used Independent student T-test analysis and linear regression analysis. Results: The study subjects consisted of 4.3% men and 95.7% women. There were no significant differences between subjects with male and female sex related to CDI-2 score, p> 0.05. The sexes of men and women have CDI-2 scores of 26.92 ± 5.02 and 26, 42 ± 3.32, respectively. There is a significant relationship between the intensity of playing video games with a CDI-2 score. Research subjects who had the intensity of playing video games for more than 2 hours a day had a higher mean CDI-2 score (28.62 ± 2.62, p <0.05) when compared to research subjects who played video games for less than 2 hours per day (26.13 ± 3.38, p <0.05). There was a significant relationship between video game content and the average CDI-2 score. Research subjects who played violent video games had higher CDI-2 scores (29.91 ± 2.07, p <0.05) when compared to groups who played video games with non-violent game themes (26, 29 ± 3.37 , p <0.05). Based on linear regression analysis, there is a relationship between the intensity of playing video games with the average CDI- 2 score (β = 1.87, SE = 0.72, p = 0.01). Meanwhile, for video game content there is no relationship between video game content containing violence and the average CDI-2 score (β = 1.91, SE = 1.21, p = 0.11). Conclusion: There is a relationship between the intensity of playing video games with the average CDI-2 score.